Metastasis from cervical carcinoma presenting with acute intestinal obstruction a case report - Datta, S; Banerjee, U; Khatua, S; Nigam, M (Bangladesh Journal of Medical Science, 2013)
A 55 yr. old woman attended emergency with acute intestinal obstruction. The patient underwent emergency surgical procedure of intestinal resection after straight X-ray,few haematological and biochemical investigations. On gross examination ileal stricture due to mass in ileocaecal region with mesenteric lymph nodes found which on histological examination came out to be a squamous cell carcinoma with metastatic deposit in lymph node. The patient had a hysterectomy done 3&1/2 years back for Stage IIB squamous cell carcinoma of cervix for which she received chemoradiation.The intestinal obstruction very likely to be a metastatic presentation. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16666 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 439-441